OPTIMALISASI DETEKSI DAN INTERVENSI DINI TUMBUH KEMBANG ANAK DI KB IT & RA/ TK IT ALAM MIFTAHUL JANNAH SURAKARTA - Enikmawati, Anik; Sri handayani; Retno Dewi Noviyanti; Nazwa Sasta Abdila; Quartiana, Rivalda Venus (P3M Universitas Aisyiyah Surakarta, 2025)
Background The results of community service activities in schools in KB IT and RA / TK IT Alam Miftahul Jannah Surakarta which were held on Friday, August 25, 2023 in 56 children, obtained 1 child experiencing developmental delays, 3 children with questionable development and 52 with development in accordance with their age. The results of this activity have been submitted to the school and used as an evaluation, that the KB IT school and RA / TK IT Miftahul Jannah Surakarta stated that teachers need to be trained in early detection and intervention of growth and development in order to monitor the growth and development of their students, with the hope of contributing to improving the quality of life of Indonesian children in the health sector. Teachers at KB IT and RA/TK IT Miftahul Jannah Surakarta conveyed that it is important to learn about the detection and intervention of growth and development of their students so that teachers' knowledge of detection and early intervention of growth and development increases so that school quality becomes good and superior in the field of child health. The purpose of training on detection and early intervention of child development is to improve the knowledge, mastery of skills of teachers of TPA IT, KB IT, and RA / TK IT Alam Miftahul Jannah Surakarta. This service method is carried out by providing training on detection and early intervention of child growth and development. The results of the Implementation of Early Growth and Development Detection and Intervention Training Activities at TPA IT, KB IT, and RA / TK IT Alam Miftahul Jannah Surakarta were carried out on Friday, September 20, 2024 at 13.00 to 16.00 WIB which was attended by a total of 8 teachers with pretest results obtained 7 (87.5%) teachers with sufficient knowledge and 1 (12.5%) teacher with less knowledge. After the presentation of basic concepts and demonstrations, an increase in knowledge of 100% of the good knowledge category was obtained.